Synthesis, Characterization and Molecular Docking Study of New Coumarin β-Thio Carbonyl Derivatives against MCF-7Breast Cancer Cell Line (Medical Forum Monthly, 2026)
Objective: To prepare and compare a set of derivatives of 7-methoxy-3-(3-(4-R-phenyl)-3-(phenylthio) propanoyl)- 2H-chromen-2-one to test their ability to induce anti-proliferative effects on MCF-7 human breast cancer cell line.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the College of Pharmacy, University of Basrah, Iraq from 15th March 2024 to 30th April 2025.Methods: Five coumarin-chalcone derivatives were prepared using starting materials. The microculture tetrazolium assay was used to determine the IC50 values of these derivatives against the MCF-7 breast cancer cell line to determine its in vitro anticancer potential. The chemical structures of the synthesized derivatives were determined by determination of the melting point, mass spectrometry, infrared spectroscopy, and nuclear magnetic resonance spectroscopy (1H and 13C). The microculture tetrazolium assay was used to assess antiproliferative activity to evaluate cell viability and calculate IC50 values.Results: Compound 11 demonstrated the best anti-proliferative activity with an IC50 of 6.25 ug/mL, compared to other derivatives. Compounds 8, 9 and 10 showed moderate cytotoxicity with the IC50 of 26.31, 29.29 and 33.49ug/mL respectively. Compound 7 on the other hand was less active with IC50 of 71.57 ug/mL. All the compounds that were synthesized showed a lower potency than the reference drug doxorubicin, the IC50 of which was 2.40 0 M.Conclusion: The antiproliferative potency of the synthesized coumarin-chalcone derivatives was different and compound 11 was the strongest against the MCF-7 breast cancer cell line. Such results indicate that additional optimization of such compounds can result in the creation of more potent anticancer agents.